An Analysis Study of Snapchat as News Source - Al - Badna, Amal Bint Mohammed; Aba Al - Khail, Hadeel bint Ibrahim (Arab Journal for Sciences and Research Publishing, 2018)
This study aims to determine the nature of Snapchat، the users، characteristics and news sources of this application as means of Social Communications، and through analysis، research and monitoring، these questions were answered about the popularity of Snapchat، and the reason that Major Media turnout to join the snapchat news platform، in addition to the technological determinism that were imposed by the application on news content.The results of the study showed that the application has a large audience of the young demographic، and Snapchat can attract young people، with its powerful and flexible tools that suits the nature of those whose accustomed to technology. Snapchat application has manage to entice the Media for the imposition of distinct content and editors with certain characteristics.
Keywords: Using Snapchat; Source; News